The implementation of physical activity policies in the Netherlands: a study applying the Physical Activity Environment Policy Index (PA-EPI) - Fleur Heuvelman; Jeroen Lakerveld; Kevin Volf; Catherine B. Woods; Suzanne van Mourik-Boelema; Saskia van den Berg; Nicolette R. den Braver (Health Research Policy and Systems)
Abstract Background Continuing high levels of population physical inactivity necessitate effective government policies to cultivate healthy physical activity (PA) environments. The Physical Activity Environment Policy Index (PA-EPI) is a monitoring framework and tool to assess the implementation of policies that promote PA. This study aims to assess the extent of PA policy implementation in the Netherlands and identify recommendations for action to improve its PA environment, using the PA-EPI. Methods The PA-EPI application was a stepwise process in which evidence of policy implementation was collected and validated by government officials. A cross-sectoral coalition of non-government independent experts then rated the extent of implementation of 45 indicators of ideal good practice, comparing them against international best practice. On the basis of these expert ratings, a scorecard categorized indicators into high, medium, low or none/very little implementation. In turn, future implementation recommendations were identified by independent experts, prioritized and disseminated. Results The evidence validation by government officials (N = 15) yielded minor changes. Independent experts (N = 14) gave 10 out of the 45 indicators a low implementation score, 28 a medium score and 7 a high score. The policy domain of transport and the infrastructure support domain of monitoring and intelligence received high implementation scores. The policy domains of mass media and workplace and the infrastructure support domains of leadership, funding and resources and workforce development received only low scores. Some domains received both high and low implementation scores (i.e. the policy domains of education and sport and recreation for all and the infrastructure support domain of governance). A total of 36 policy recommendations and 26 infrastructure support recommendations were identified. The top prioritized policy recommendations fell within the urban design, education, transport, and sport and recreation for all domains. For infrastructure support, the top prioritized recommendations related to the leadership, funding and resources, and governance domains. Conclusions The results reveal important policy implementation gaps and strengths across several domains in the Netherlands. Prioritized recommendations are provided for the government to address these implementation gaps and monitor policy change.